Research methods and applications for student affairs - Biddix, J. Patrick (Jossey-Bass, a Wiley Brand, 2018)
The text reviews the basics of these qualitative and quantitative approaches and explores how to differentiate the major types of research as well as how to understand, read, evaluate, and apply results. Biddix also includes important information on using mixed methods approaches. Research Methods and Applications for Student Affairs is an essential guide for enhancing research methods' skills, and offers direction for applying those skills in actual work situations.